2008
DOI: 10.1111/j.1464-5491.2007.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in height explain gender differences in the response to the oral glucose tolerance test— the AusDiab study

Abstract: Men and women had different glycaemic profiles; women had higher mean 2hPG levels, despite lower fasting levels. It appeared that the higher 2hPG levels for women related to lesser height and may be a consequence of using a fixed glucose load in the OGTT, irrespective of body size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
99
7
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 40 publications
13
99
7
1
Order By: Relevance
“…Our results support the findings from the AusDiab study [1], indicating that sex differences in 2hPG levels are explained by differences in height between men and women. The authors of the AusDiab study suggest that the inverse association between height and 2hPG levels reflects the larger amount of metabolically active tissue that tall individuals have available for metabolising the fixed amount of glucose compared with short individuals.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results support the findings from the AusDiab study [1], indicating that sex differences in 2hPG levels are explained by differences in height between men and women. The authors of the AusDiab study suggest that the inverse association between height and 2hPG levels reflects the larger amount of metabolically active tissue that tall individuals have available for metabolising the fixed amount of glucose compared with short individuals.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, our study showed that men had higher 2hPG levels than women for a given height. Therefore, sex differences in 2hPG and in the prevalence of i-IGT, as documented in previous studies [1][2][3], are probably not related to sex-specific differences in the physiology of glucose regulation. This finding was further supported by the fact that more women than men with i-IGT had HbA 1c levels <6.0% and that 2hPG levels were higher in women than in men, despite lower or similar HbA 1c levels (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations